Jakość w medycynieEuropean Working Time Directive: how to improve cardiothoracic training for SpRs and SHOs - Szafranek, Andrzej; Yusuf, Mohamed M.; Olszówka, Piotr; Lucraz, Heyman; Dimitrikikakis, George; O’Keefe, Peter A. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Objective: Reduction in surgical training time due to EWTD mandates a review of the use of training time. The activity of cardiothoracic SpRs on the Cardiac Intensive Therapy Unit (CITU) was audited. Aim: Study aims were to identify any potential benefits in cardiothoracic training, and to investigate mechanisms of communication between CITU staff and overall effect on patient care. Method: All calls from the Cardiac Intensive Therapy Unit (CITU) to a surgical resident were assessed by nurses and surgeons (n=120). All calls were classified as: routine (predicted, non-urgent), urgent (non-life-threatening) or emergency (surgical, life-threatening). A dedicated questionnaire based on the most common postoperative complications was devised to examine knowledge of CITU staff (surgical and anaesthetic Specialist Registrars (SpRs), surgical Senior House Officers (SHOs) and CITU senior nurses). Results were analyzed and statistical comparison was made using T test. Results: Most calls during the day were routine (n=97, 81%). Urgent calls (n=18, 15%) were less common; most were during the night (n=13, 73%). In 5 cases surgical attention was necessary (4%) and in 2 a cardiothoracic SpR needed to be involved taking the patient to the theatre (1.6%). There was a significant difference in the nature of calls between night and day. There was a statistical difference in results of the questionnaire between SHO and other groups (p<0.01). Conclusions: Our study indicated that there is no need for cardiothoracic SpRs to be resident on the CITU during the daytime. For surgical SHOs there is an opportunity to improve critical care knowledge and skills. Support of the anaesthetist and senior nursing staff can provide safe patient care at the CITU.